SOCIAL PRACTICES OF ACTORS IN THE COMMUNITY OF GENERASI BARU INDONESIA XI UNIVERSITAS SUMATERA UTARA IN THE ZERO WASTE LIFESTYLE PHENOMENON - Nurul Inayah Zul Putri; Rahman Malik; Rizabuana Ismail; T. Ilham Saladin (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study aims to understand how members of the Generasi Baru Indonesia XI Universitas Sumatera Utara (GenBI XI USU) community engage in social practices related to the implementation of a zero waste lifestyle. The research addresses the issue of high waste production in Medan City and explores how youth communities respond to environmental challenges through sustainable living. A qualitative approach with a phenomenological method was used to explore the subjective experiences of community members. Data were collected through participatory observation, semi-structured interviews, and documentation involving GenBI members who apply the 5R principles: refuse, reduce, reuse, recycle, and rot. The analysis was conducted using Pierre Bourdieu’s theory of social practice, focusing on the concepts of habitus, capital, and field. The findings reveal that the formation of a zero waste habitus is influenced by family experiences, educational environments, and community activities. Social, cultural, economic, and symbolic capitals significantly support the sustainability practices adopted by community members. Moreover, the zero waste lifestyle becomes a site of symbolic contestation within the community, allowing members to demonstrate environmental awareness and strengthen their identity as responsible youth. This study highlights the role of communities as agents of change in fostering ecological habits through the internalization of sustinable values and practices within their social fields.